THE METRIC DIMENSION OF A GRAPH COMPOSITION PRODUCTS WITH STAR - Saputro, S.W.; Suprijanto, D.; Baskoro, Edi Tri; Salman, A.N.M. (IndoMS, 2012)
looked at pdf abstractDOI :Â http://dx.doi.org/10.22342/jims.18.2.114.85-92